Flexural Strength of RHS Perforated Lean Duplex Stainless Steel Beam at Temperature 24-900ºC - Kelsen Andrian Priestley; Andy Prabowo (Institute of Research and Community Outreach - Petra Christian University, 2024)
The investigation of stainless steel structures at elevated temperatures is still limited, especially to those focused on the behaviour of perforated beams. Therefore, a numerical study was conducted to investigate the behaviour and strength of cold-formed lean duplex stainless steel (CFLDSS) beams having a single web perforation that failed due to pure bending at temperatures between 24-900oC. In total, 200 square and rectangular hollow sections (RHSs), which had various cross-section sizes, hole diameters, and temperature simulations, were involved in the parametric study. The numerical study was based on the ABAQUS simulation results of the 200 specimens. The numerical model was developed based on the validated existing studies. Numerical evaluations show that the existing codified strength predictions are conservative, but it has inconsistent safety. Hence, this study suggests modifications to the existing strength prediction, which is more conservative and reliable.